2021
DOI: 10.1038/s41598-021-87667-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional NMDA receptors are expressed by human pulmonary artery smooth muscle cells

Abstract: N-methyl-d-aspartate (NMDA) receptors are widely expressed in the central nervous system. However, their presence and function at extraneuronal sites is less well characterized. In the present study, we examined the expression of NMDA receptor subunit mRNA and protein in human pulmonary artery (HPA) by quantitative polymerase chain reaction (PCR), immunohistochemistry and immunoblotting. We demonstrate that both GluN1 and GluN2 subunit mRNAs are expressed in HPA. In addition, GluN1 and GluN2 (A–D) subunit prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“… 4 GluN1 and all four GluN2 subunits were also expressed in the human pulmonary artery smooth muscle cells. 22 Overall, these findings indicate that NMDA receptors could control the respiratory tract function in vertebrate animals. 23 …”
Section: Expression Of Nmda Receptors In the Human Lungsmentioning
confidence: 85%
“… 4 GluN1 and all four GluN2 subunits were also expressed in the human pulmonary artery smooth muscle cells. 22 Overall, these findings indicate that NMDA receptors could control the respiratory tract function in vertebrate animals. 23 …”
Section: Expression Of Nmda Receptors In the Human Lungsmentioning
confidence: 85%
“…Studies performed on rodent models and cell lines have shown that the predominant site of action for ketamine is neurons due to expression pattern of ketamine receptors. However, recent studies demonstrated extraneuronal sites for ketamine 51 . Our findings suggest that ketamine is likely to act nonautonomously to induce vulval and cuticular changes.…”
Section: Discussionmentioning
confidence: 99%
“…These cells have been reported to cause constrictions in the airway by activating the NMDA receptor. [24,25] ARS has an antagonistic effect on NMDA receptors. It has also been reported that the blockade of the NMDA receptor prevents oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA receptors are known for their function in neurons and their role in the pathophysiology of epilepsy. [13,24] However, studies on its presence in the lung and other tissues are limited. A recent study identified lung smooth muscle cell types that express NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%